Carcinogenicity of food mutagens. - Sugimura, T (1996)
Cancer cells are produced by the accumulation of genetic alterations in somatic cells. Those genetic alterations are produced by xenobiotics, which enter the human body from the environment, and by autobiotics, which are produced in the human body. Food contains many different types of xenobiotic mutagens/carcinogens and tumor promoters. Food can influence the formation of autobiotic mutagens/carcinogens and give rise to tumor-promoting conditions. In spite of this, it can also contain many antimutagenic, anticarcinogenic, and antitumor-promoting substances. Carcinogenic risk and anticarcinogenic efficacy are hard to express quantitatively; however, holistic approaches that are designed to improve lifestyle are realistic for cancer prevention.